2020
DOI: 10.1186/s12891-020-03512-x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activation patterns during backward walking in people with chronic ankle instability

Abstract: Background: Altered walking patterns are often described in individuals with chronic ankle instability (CAI). Contemporary treatment paradigms recommend backward walking (BW) to improve locomotion in people with musculoskeletal disorders. The purpose of this study was to determine whether muscle activity and activation variability during BW differs between subjects with and without CAI. Methods: Sixteen participants with CAI and 16 healthy controls walked on a treadmill at their self-selected speed under BW an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…However, the results from our muscle activation during walking should be interpreted cautiously. For example, our results are not in line with researchers who reported a decrease in peroneus longus during the initial stance 13 , 60 , or lack of difference between the groups 20 , 21 , 42 , 43 . The variations in the reference task adopted for EMG normalization by different researchers induce a problematic comparison of results across studies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the results from our muscle activation during walking should be interpreted cautiously. For example, our results are not in line with researchers who reported a decrease in peroneus longus during the initial stance 13 , 60 , or lack of difference between the groups 20 , 21 , 42 , 43 . The variations in the reference task adopted for EMG normalization by different researchers induce a problematic comparison of results across studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results about the trend of activation coefficients also reflect that the corresponding modules of modulation activation have similar relationships in different individuals, with the CNS as the control center of human movement production modulation. Furthermore, the activation coefficient changes with time, which reflects the changing excitation contribution of each module to the muscle synergy mode ( Geyer and Herr, 2010 ; Balasukumaran et al, 2020 ). However, the relationship between the activation scale and the neural control remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that CAI had lower PL EMG-amplitude variability from 1 to 10 %, 32-38 % and 56-100 % of the gait cycle when compared to the controls [37]. In contrast, another study [38] found no difference between CAI and the controls in the PL, TA, MG, and GM activation variability in backward and forward treadmill walking, nor in the activation magnitude of the muscles. The timing of activation during treadmill walking was investigated in one study [36], which reported that PL, TA, LG, RF, BF, and GM were activated earlier in CAI than in the control participants and PL was activated for a longer time interval across the entire stride cycle in CAI compared to the controls [36].…”
Section: Muscle Activations During Gaitmentioning
confidence: 94%